PREDICTING ATTITUDE TOWARD COVID-19 VACCINE AMONG INDONESIANS: AN APPLICATION OF THE THEORY OF PLANNED BEHAVIOR - Husna, Aftina Nurul; Zahra, Aning Az; Akmal, Nur; Ningrum, Milyarti (Faculty of Psychology, Universitas Diponegoro, 2022)
Vaccination is an important tool to end the pandemic; however, various surveys show considerable cases of hesitance and refusal among public in many countries. This study aimed to predict the effect of several factors on attitudes toward the Covid-19 vaccine using the theory of planned behavior framework. A quantitative survey design was used to collect data from participants from 15 cities in Indonesia (n = 323) during the second wave of pandemic in June-July 2021. Data were analyzed using hierarchical multiple regression to test three models. In Model 1, risk perception and confidence in vaccine significantly predict attitude toward vaccine, Adj. R2 = .501, F(2, 320) = 162.610, p < .000. In Model 2, adding trust to government does not improve the prediction, Adj. R2 = .504, ΔR2 = .003, F for R2 Change = 3.284, p = .071. In Model 3, we added knowledge about Covid-19 and beliefs in conspiracy in the model, which presented as the best model by having Adj. R2 = .532, ΔR2 = .030, F for R2 Change = 10.222, p < .000. Though relatively weaker than the influence of risk perception, t(317) = 4.250, p < .00, and confidence in vaccine, t(317) = 10.24, p < .00, knowledge about Covid-19 can predict attitude toward vaccine t(317) = 4.521, p < .00, while beliefs in conspiracy do not. It is concluded that there is an interplay between control beliefs (knowledge) and behavioral beliefs (risk perception and confidence in vaccines) in shaping attitudes toward a vaccine. Confidence in vaccines plays the most important role, followed consecutively by risk perception and knowledge. It suggests that health authorities emphasize the safety and efficacy of vaccinesin reducing the risk of disease while educating the public with authorized information.